Bacterias oportunistas y microbiota en niños con leucemia y enterocolitis neutropénica - Guadalupe García-Elorriaga (Revista Médica del Instituto Mexicano del Seguro Social, 2013)
Objective: to determine the prevalence of opportunistic microorganisms and microbial fl ora in neutropenic enterocolitis in oncohematological pediatric patients.Methods: a prospective and observational study was done. Patients with diagnosis of acute leukemia and neutropenia were included. Stool cultures were taken to identify microorganisms and microbial fl ora. 2 test with Yates corrections and Fisher exact test were used in the statistical analysis.Results: twenty-one patients were included (12 male, 57.1 %). The stool cultures showed that 68 % of microorganisms were gram negative. The presence of microorganisms gram positive was of 20 %, 6 % for Candida sp.; 3 % for Cryptosporidium sp.; and in 3 % were observed acid fast bacilli. Staphylococcus epidermidis, Enterobacter sp. and Escherichia coli were presented in pure culture. No association was found between microorganisms gram positive and gram negative with the age, white cell count or pure or mixed culture.Conclusions: although gram negative microorganism were the most frequent, gram positive and other microorganisms that are not detected habitually in feces culture were isolated.